Fifteen years looking at the mirror: On the presence of PISA in education policy processes (Portugal, 2000‐2016). (11th April 2017) - Carvalho, Luís Miguel; Costa, Estela; Gonçalves, Catarina
Abstract: This article describes and discusses what happens when knowledge for policy generated within PISA is received by its target audience: what have the Portuguese policy actors been doing with PISA data and analysis when they consider, express and justify their choices? Drawing on previous and current studies, using interview materials and formal and informal policy documents, as well as texts published in the written press, the article analyses two main phenomena related to the reception of PISA and how this has evolved between 2001 and 2012 in Portugal: the consolidation of PISA's credibility as a source for policy processes and texts; the emergence of new actors and modes of intervention in the production of knowledge for national policy, drawing on PISA. Finally, it presents an analysis of the reception of PISA 2015 in the Portuguese media, focusing on the interventions by political actors in the Portuguese daily and weekly written press. Two main elements emerge from our content analysis as the main common elements of that reception: the consecration of PISA's credibility; and the practices of qualification and disqualification of educational policies and perspectives. The article concludes by emphasising the regulatory role of PISA in Portuguese policy processes and the relevant contribution played by the politics of reception in legitimising this role.